Smallholder Broiler Farmers' Characteristics to Uptake Measures Against Highly Pathogenic Avian Influenza in Western Java - Pramuwidyatama, M. Gumilang; Indrawan, Dikky; Saatkamp, Helmut W.; Hogeveen, Henk (Frontiers in Veterinary Science, 2022)
Highly Pathogenic Avian Influenza (HPAI) H5N1 remains endemic in the Western Java smallholder broiler farms. This study aims to identify farmers and farm characteristics associated with farmers’ motivations towards five different measures directed to HPAI: cleaning and disinfection (C&D), vaccination, reporting, and stamping-out with and without compensation. Through multi-stage sampling and a questionnaire, we collected data from 199 farmers in Western Java and applied descriptive analysis and logistic regression to evaluate the data. Most smallholder broiler farms had a production contract with a poultry company. Unexpectedly, we identified subtypes of price-contract (i.e., revenues based on contract selling price and live bird weight) and makloon-contract (i.e., revenues based on management fee per bird) schemes. We identified these new subtypes as extended price-contract and extended makloon-contract schemes. These extended subtypes included issues related to animal health management and payment schemes. The results show that most of the farmers in both extended types were highly motivated to implement C&D and vaccination. Business types and farmers’ awareness of HPAI were significantly associated with a farmer’s motivation to implement C&D. Farmers who had an awareness of HPAI were more likely to implement C&D. Although our models were insufficient to model the association of farmers’ motivation to uptake preventive measures against HPAI in Western Java, this study identified significant characteristics that help improve HPAI control policy in Western Java. Our study suggests that farm business types and incentives through payment schemes and training may increase the uptake of preventive measures by farmers.